Pengaruh Presepsi Fitur Flash Sale Dan Gratis Ongkir Shopee Terhadap Loyalitas Pelanggan yang Dimediasi Kepuasan Konsumen di Kota Padang - Syazwana Syazwana; Fitria Ridhaningsih (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to directly demonstrate the influence of Shopee's flash sale and free shipping features on customer loyalty, mediated by customer satisfaction in Padang City. This study used 180 respondents who regularly accessed and shopped through the Shopee marketplace in the last six months. The sampling technique used was purposive sampling. Data collection was carried out by distributing questionnaires via Google Form. The data analysis techniques used in this study were Structural Equation Modeling (SEM) and T-statistic testing. In accordance with the hypothesis testing, it was found that the perception of the flash sale feature had a positive effect on customer satisfaction but did not affect customer loyalty. In the hypothesis testing stage, free shipping also found a positive effect on customer satisfaction or loyalty. In the indirect effect testing stage, it was found that satisfaction was unable to mediate the relationship between the perception of the flash sale feature and customer loyalty, but customer satisfaction was able to mediate the relationship between free shipping and customer loyalty in Padang City in online shopping through the Shopee marketplace.